2019
DOI: 10.1038/s41586-019-1441-7
|View full text |Cite|
|
Sign up to set email alerts
|

Observed controls on resilience of groundwater to climate variability in sub-Saharan Africa

Abstract: Groundwater in Africa supports livelihoods and poverty alleviation 1,2 , maintains vital ecosystems, and strongly influences terrestrial water and energy budgets 3. However, hydrologic processes governing groundwater recharge sustaining this resource, and their sensitivity to climatic variability, are poorly constrained 4,5. Here we show, through analysis of multi-decadal groundwater hydrographs across sub-Saharan Africa, how aridity controls the predominant recharge processes whereas local hydrogeology influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
131
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(155 citation statements)
references
References 46 publications
(39 reference statements)
10
131
0
1
Order By: Relevance
“…The water content of the subsurface can be separated in two components: the root zone soil moisture obtained from the Global Land Evaporation Amsterdam Model 25 (see supporting document for details of the GLEAM dataset), and the groundwater after removal of the root zone soil moisture from the subsurface storage. We estimate that Lake Chad's root zone soil moisture represents only 0.65 km 3 of the total annual amplitude, meaning that TWS variations are mostly driven by the changes in groundwater which is in agreement with groundwater data observations from Sahel 26 . Lake Chad's SWS and TWS exhibit similar time-variations (R = 0.81 over a 13-year period with one month of time lag).…”
Section: Surface and Sub-surface Water Volume Variationssupporting
confidence: 89%
“…The water content of the subsurface can be separated in two components: the root zone soil moisture obtained from the Global Land Evaporation Amsterdam Model 25 (see supporting document for details of the GLEAM dataset), and the groundwater after removal of the root zone soil moisture from the subsurface storage. We estimate that Lake Chad's root zone soil moisture represents only 0.65 km 3 of the total annual amplitude, meaning that TWS variations are mostly driven by the changes in groundwater which is in agreement with groundwater data observations from Sahel 26 . Lake Chad's SWS and TWS exhibit similar time-variations (R = 0.81 over a 13-year period with one month of time lag).…”
Section: Surface and Sub-surface Water Volume Variationssupporting
confidence: 89%
“…While climate change models show diverging trends of more dry or more wet conditions and changes in the seasonality, the impact of conversion from natural LULC into agricultural utilized fields is more explicit [3,4,81], although it still depends on the specific crops grown. Nevertheless, intensification of precipitation might foster groundwater recharge and therefore access to renewable water resources in the Kilombero Catchment as well as already described in other catchments in SSA [87]. This indicates a particular resilience to climate change and intensification of precipitation events.…”
Section: Land Use/cover and Climate Change Impact Assessment On Watermentioning
confidence: 68%
“…This indicates a particular resilience to climate change and intensification of precipitation events. However, more observation-driven research is needed on the relation of surface water and groundwater resources on this topic [87]. Moreover, data availability on the hydrogeology of the Kilombero Catchment is still poor to be modeled precisely, although some data and a local conceptual model exists [88,89].…”
Section: Land Use/cover and Climate Change Impact Assessment On Watermentioning
confidence: 99%
“…Back et al 2018). The reasons for this are uncertain, but could be linked to more intense rainfall and/or flooding under wetter conditions (Bridgman et al 1995, Wu et al 2016 and the activation of rapid recharge pathways and/or shallower groundwater tables under wetter climate conditions (Gotkowitz et al 2016, Cuthbert et al 2019. It has been previously suggested that under wetter climatic conditions, microbiological contamination may be higher (Gotkowitz et al 2016), and with higher contamination during the wet season (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the quantity and accessibility of groundwater available for rural community supplies in Africa has been the primary focus of regional research to date (e.g. Macdonald et al 2012;Bonsor et al 2018, Cuthbert et al 2019. In contrast, the quality (both chemical and microbiological) of groundwater resources in Africa has tended to focus on areas with known natural water quality problems such as arsenic and fluoride (Reimann et al 2003, Edmunds and Smedley 2005, 2013, Rango et al 2013, contamination from mining (Smedley 1996, Von Der Heyden andNew 2004) or urbanisation (Lapworth et al 2017a).…”
Section: Introductionmentioning
confidence: 99%